Effect of muscle tone on ankle kinetics during gait with ankle-foot orthoses in persons with stroke. Issue 8 (17th November 2017) - Mizuno, Shiho; Sonoda, Shigeru; Takeda, Kotaro; Maeshima, Shinichiro
Abstract: Background: Individuals exhibiting hemiplegia and increased ankle plantar flexors muscle tone following stroke are frequently prescribed an ankle-foot orthosis (AFO) to regain functional ambulation. The effect of muscle tone on ankle kinetics when walking with an AFO remains unknown. Objectives: To investigate the effect of plantar flexion (PF) muscle tone on ankle plantar flexion torque during walking with an ankle-foot orthosis Methods: The study included 80 participants with first-ever stroke whose manual muscle testing (MMT) of ankle DF 0-4, and 10 healthy subjects. Participants were instructed to walk on a treadmill, at a comfortable speed, wearing an instrumented AFO. Minimum PF torque during the last half of swing was extracted as an outcome measure. Resistive PF torques during passive slow and fast stretches were measured with a custom-built device, with torques at 10° DF (T10°-slow and T10°-fast) extracted as defining parameters for stiffness and muscle tone, respectively. Results: Correlations between both T10°-slow and T10°-fast variables with minimum PF torque were fair among ankle DF MMT 0–3 groups ( r = 0.71 −0.74, p < 0.01), with no correlation observed among the MMT 4 group and healthy subjects. Conclusions: Effects of muscle tone on ankle kinetics during swing phase, with an AFO, were observed in persons with severe ankle DF paresis. Quantitative evaluation of ankle kinetics during gait with an AFO in addition to evaluation of muscle tone at rest is contributory to objective assessment of a muscle tone, not subjective rating scale at rest, or visual inspection of walking.